An application of improved space vector strategy based in digital direct synthesizers for a high-performance inverter. (May 2021) - Silva, Rodrigo; Huerta-Ruelas, Jorge A.; de Dios Ortiz-Alvarado, Juan; Mendoza-Mondragon, Fortino; Zavala, Antonio Hernández
Abstract: When performing commutation at induction motors based in PWM, a change in the switching frequency can take several clock cycles to be reflected in the windings generating harmonics that could damage the motor or generate an erroneous modulation. Most of the high-performance inverters use the Space Vector PWM given its minor switching losses and its capability to reduce the harmonics in the output signals. Nonetheless, the SVPWM requires complex calculation in online operation, which is the major concern for real-time implementations. Even that there are problems related to the development of technology that does not use the sine waveform to drive an induction motor and considering the availability and capability of Direct Digital Synthesizers (DDS) technology, we developed a hardware–software system to propose a modulation strategy called Space Vector DDS. The SVDDS can synthesize any digital waveform besides the sine waveform, becoming a more versatile approach. This proposal is the first one to couple the DDS in the commutation of an induction motor. As summary, the main features of our SVDDS system are its capability to synthesize any discrete waveform, improvement of control response parameters (13% for a load test and 12% for a speed test, compared with SVPWM), a low value of the total harmonic distortion index (4.88%) and reduction of the mathematical processing (system response of 21.364 ns). Highlights: Induction motor controller without using the PWM peripheral. Induction motor controller with the ability to generate different waveforms. Depending of shape of the discrete waveform change the performance of the system. Controller hardware develop in FPGA technology. Induction motor controller based in space vector technique.